Faktor-Faktor yang Mempengaruhi Kepuasan Pasien Badan Penyelenggara Jaminan Sosial pada RSUD Padang Pariaman - Yulina Eliza; Edra Lina; Irnovriadi Irnovriadi; Jasmalinda Jasmalinda (Target : Jurnal Manajemen Bisnis, 2022)
This study aims to determine the effect of competence, interpersonal communication and service quality on BPJS patient satisfaction at Padang Pariaman District Hospital. The method used in this research is quantitative research with a descriptive and associative approach. The population in this study were 8,462 patients who came during 2021. The sample used was 100 people using a purposive sampling technique. The data analysis technique uses multiple linear regression. The results of the study show that: (1) Competence has a positive and significant effect on BPJS patient satisfaction at Padang Pariaman District Hospital. (2) Interpersonal communication has a positive and significant effect on BPJS patient satisfaction at Padang Pariaman District Hospital. (3) Service quality has a positive and significant effect on patient satisfaction at the BPJS RSUD Padang Pariaman Regency. (4) Competence, interpersonal communication and quality of service simultaneously have a positive and significant effect on patient satisfaction at the BPJS RSUD Padang Pariaman Regency. The conclusion of the research results shows, the higher the competence, the higher patient satisfaction, conversely the lower the competence, the lower patient satisfaction. The better the interpersonal communication, the higher the patient satisfaction, conversely the worse the interpersonal communication, the lower the patient satisfaction. The higher the quality of service, the higher the patient satisfaction, conversely the lower the quality of service, the lower the patient satisfaction.